Navigation Composite faces are not (necessarily) processed coactively: A test using systems factorial technology and logical-rule models. - Xue Jun Cheng; McCarthy, Callum J.; Wang, Tony S. L.; Palmeri, Thomas J.; Little, Daniel R. (Journal of Experimental Psychology. Learning, Memory & Cognition, 2018)
Upright faces are thought to be processed more holistically than inverted faces. In the widely used composite face paradigm, holistic processing is inferred from interference in recognition performance from a to-be-ignored face half for upright and aligned faces compared with inverted or misaligned faces. We sought to characterize the nature of holistic processing in composite faces in computational terms. We use logical-rule models (Fifić, Little, & Nosofsky, 2010) and Systems Factorial Technology (Townsend & Nozawa, 1995) to examine whether composite faces are processed through pooling top and bottom face halves into a single processing channel--coactive processing--which is one common mechanistic definition of holistic processing. By specifically operationalizing holistic processing as the pooling of features into a single decision process in our task, we are able to distinguish it from other processing models that may underlie composite face processing. For instance, a failure of selective attention might result even when top and bottom components of composite faces are processed in serial or in parallel without processing the entire face coactively. Our results show that performance is best explained by a mixture of serial and parallel processing architectures across all 4 upright and inverted, aligned and misaligned face conditions. The results indicate multichannel, featural processing of composite faces in a manner inconsistent with the notion of coactivity.